1999
DOI: 10.1002/(sici)1097-4644(19991001)75:1<22::aid-jcb3>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of the osteoblast phenotype in primary human osteoblasts in culture: Comparison with rat calvarial cells in osteoblast differentiation

Abstract: In rat osteoblast-like cells, a time-dependent sequence of growth and differentiation-dependent genes has been identified and a model of osteoblast differentiation in culture suggested. We investigated the expression of the bone matrix-associated proteins osteonectin and procollagen I and of the bone cell phenotype-related proteins alkaline phosphatase and osteocalcin during cell culture in primary human osteoblast like cells. Primary human explant cultures from nine young healthy donors were established under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
1
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 61 publications
8
48
1
9
Order By: Relevance
“…Except for some small donor-dependent variations, no cytotoxic effects on pHOB cell density, morphology and viability could be observed during incubation with COOL formulation A independent on the setting time. In accordance to Siggelkow et al 30 , pHOB cells from both donors showed a typical long-stretched fibroblast-like appearance during early proliferation, which switched to polygonal during continuing proliferation. In contrast, pHOB cells incubated with Refobacin ® R added to the cultures directly after preparation showed extremely high death rates, probably due to chemical necroses caused by the release of free, not polymerized, toxic MMA monomers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Except for some small donor-dependent variations, no cytotoxic effects on pHOB cell density, morphology and viability could be observed during incubation with COOL formulation A independent on the setting time. In accordance to Siggelkow et al 30 , pHOB cells from both donors showed a typical long-stretched fibroblast-like appearance during early proliferation, which switched to polygonal during continuing proliferation. In contrast, pHOB cells incubated with Refobacin ® R added to the cultures directly after preparation showed extremely high death rates, probably due to chemical necroses caused by the release of free, not polymerized, toxic MMA monomers.…”
Section: Discussionsupporting
confidence: 88%
“…Another component of the ceramic mixture is CZP, which is biostable 2,30 and increases the radiopacity of COOL. It accounts for less than 10 wt.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of an earlier study on the proliferation and differentiation of osteoprogenitor cells in the presence or absence of dex [32], CFU-O were not detectable beyond 18-20 population doublings. It is also of interest that in the hematopoietic system dex in combination with erythropoietin and stem cell factor was able to induce erythroid progenitors to undergo a similar number of cell divisions (15)(16)(17)(18)(19)(20)(21)(22), corresponding to a 10 5 -10 6 -fold amplification before a loss in proliferation and differentiation capacity was measured [43]. Dex acts directly on human erythroid progenitors, maintaining their colony-forming capacity and delaying their differentiation, with the glucocorticoid receptor acting as a key regulator for the decision between self-renewal and differentiation [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying a relationship between population growth, nodule formation, and expression of surface or other osteoblast markers is the object of much study [15,16,28,[49][50][51][52]. To this end, separation of the input RC population into four purified fractions (ALP showed that nodules are able to form within each fraction [53].…”
Section: Of Mineralized Nodules After 21 Days In Vehicle (Hatched) Ormentioning
confidence: 99%
“…During proliferation, the production of collagen I initially occurs, followed by an increased in the expression of ALP and calcium deposition (28). Collagen I comprises approximately 90% of the organic material as the most abundant protein component of the bone matrix.…”
Section: Discussionmentioning
confidence: 99%